The competitive dimension of comparative optimism / La dimensión competitiva del optimismo comparativo. Issue 1 (2nd January 2019) - Krzeminski, Aurélie; Milhabet, Isabelle; Priolo, Daniel
Abstract: We usually think that positive events are more likely to occur to us than to others and vice versa for negative events. This phenomenon, called comparative optimism, increases both social utility and the tendency to present oneself as above average. The literature highlights the same elements in competition. Our objective was to study the links between comparative optimism and competition and to argue that social utility can explain this relation. In our study, we presented participants with comparative optimistic, comparative pessimistic or neutral targets. We observed that a comparative optimistic target was perceived to fit better with a competitive situation than other targets because he/she was deemed socially useful (e.g., assertive, self-confident). Participants also felt that a comparative optimistic target pursued more performance goals than the other targets. This effect was mediated by the perception of this target as a competitive person. These results, consistent with our assumptions, highlight the competitive dimension of comparative optimism.